Pengembangan Kreativitas dan Life Skills Siswa Melalui Kerajinan Tangan Berbasis Pemanfaatan Barang Bekas - Ummi Inayati; Lina Agustina; Devi Maulidina; Ina Nopia Dinta; Isnatur Rhohmah; Izzatul Ilarifa; Lailatu Sya’diyah; Syadidul Fikri Zamroni; Riska Alfiyah Rohmatin; M. Syahrul Fajar; Ednandia Khabibatu Ulla (Transformative Service Journal, 2025)
This community service program is important because it aims to foster students’ creativity while simultaneously instilling environmental awareness through the utilization of recyclable materials available in their surroundings. The activity was carried out at MI Islamiyah Karangdowo, Sumberrejo District, Bojonegoro Regency, involving 50 students from grades 4, 5, and 6. The method used was the Asset-Based Community Development (ABCD) approach, which emphasizes the utilization of assets and potentials already possessed by the partners as sustainable development capital. The implementation of the program resulted in tangible products, namely flower pots made from used bottles (20 pieces) by grade 4 students, tissue holders from ice cream sticks and used cardboard (15 pieces) by grade 5 students, and photo frames from cardboard and seeds (15 pieces) by grade 6 students. The results indicated an increase in students’ creative skills, the growth of environmental cleanliness awareness, and stronger collaboration between teachers and students. The handicraft products created were not only functional and aesthetically valuable but also provided students with hands-on experience in managing recyclable materials creatively. In addition, teachers were motivated to integrate creativity-based learning into the teaching process. The positive impacts of this program can be seen in students’ behavioral changes toward waste management, improved creative abilities, and the creation of an innovative learning atmosphere. Program sustainability is planned through integration into the local content curriculum, the establishment of a creative school community, and the development of partnerships with external parties.